(3GdUchc hGdTQhWs - (3HOQ GdOjf MSf Hf Rjf GdOjf YeQ GHf MHjH GdMdHjs ((3CMeO Hf LYaQ GdMfai GdHTcWGTi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje , GdMeO ddg GdPi gOGfG Edi SHjd GdQTGO CeG HYO agPg QSGdI ai Yde GdTQhW GdeJYdbI HGdeYGedGJ hGdYbhO eTJedI Ydi EjLGR hGNJUGQ s
(3BNQgG (B:s
(3KHhJ hMce HJGQjN cPG JeJ HYhf Gddg JYGdi hMSf Jhajbg hCTgO Cf dG Edg EdG Gddg hMOg dGTQjc dg hCTgO Cf SjOfG eMeOkG YHOg hQShdg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdESdGejs